Pengaruh Profitabilitas, Leverage, dan Earning Per Share (EPS) terhadap Harga Saham Perusahaan Sektor Teknologi yang Terdaftar di BEI - Firansiska Sukirno, Adelia; Takarini, Nurjanti (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2025)
This study aims to examine the influence of profitability, leverage, and Earning Per Share (EPS) on stock prices within an industry. The ratios used as independent variables are Return On Asset (ROA), Debt to Equity Ratio (DER), and EPS (market ratio), while the dependent variable is stock price. The research focuses on companies in the technology sector that actively trade shares and are listed on the Indonesia Stock Exchange (IDX) during the period from 2019 to 2021. The data collection method used is purposive sampling with a quantitative approach employing multiple linear regression analysis using SPSS version 23. Based on the results of the analysis, It was found that the variables profitability and leverage did not contribute to the stock prices of technology sector companies. Meanwhile, EPS contributed to the stock prices of technology companies listed on the Indonesia Stock Exchange (IDX).